Molecular Dynamical Simulations of the Structural and Melting Properties of $Al_{196}$ Cluster (Journal of Atomic and Molecular Sciences, 2013)
Based on the Gupta-type semi-empirical inter-atomic many-body potential,the melting behaviors of the $Al_{196}$ cluster are systematically studied by using themolecular dynamics method combined with the annealing and quenching techniques.Our simulation results show that from different initial structures one can observe quitedifferent melting behaviors. From a relatively low-energy stable geometry, two peaksoccur clearly in the heat capacity curve; But only one peak dominates the heat capacitycurve if starting from the ground-state or its closer low energy structures. Reasonsof the different melting properties of the Al196 cluster are explored by analyzing theenergy distributions of the simulated quenching structures of $Al_{196}$ at different temperatures.
Keywords: Gupta potential; cluster; molecular dynamics; melting.